Exogenous Insulin Injection-Induced Stiff-Person Syndrome in a Patient With Latent Autoimmune Diabetes: A Case Report and Literature Review - Lee, Yi-Yin; Lin, Cheng-Wei; Chen, I-Wen (Frontiers in Endocrinology, 2020)
Stiff-person syndrome (SPS) is highly associated with anti-glutamic acid decarboxylase (GAD) antibody. However, GAD antibodies alone appear to be insufficient to cause SPS, and they possibly are involved in only part of its pathophysiology. It is suspected that the symptoms of SPS get precipitated by external stimuli. Here, we briefly introduce the case of a patient with latent autoimmune diabetes who developed SPS through the action of subcutaneously injected insulin. A 43-year-old man was diagnosed with diabetes and initially well-controlled with oral hypoglycemic agents but progressed to requiring insulin within 1 year of diagnosis. Two months after the initiation of basal insulin therapy, he presented with abdominal stiffness and painful muscle spasms, involving the lower limbs, which resulted in walking difficulty, and thus, he refused insulin injections thereafter. He had been treated with oral antidiabetic agents instead of insulin for 10 years until premixed insulin twice daily was started again due to poor diabetes control. Immediately after insulin injection, abdominal muscle rigidity and spasms were noted. When insulin was not administered, frequent episodes of diabetic ketoacidosis occurred. Serum GAD antibody test was positive and there was no positivity for islet antigen-2 antibody. A glucagon stimulation test demonstrated relative insulin deficiency, indicative of latent autoimmune diabetes in adults (LADA). Tolerable muscle rigidity was achieved when the dosage of basal insulin was split into two separate daily injections with lower amounts of units per injection. This case highlights a different form of autoimmune diabetes in SPS. To our knowledge, this is the first report of SPS described shortly after the initiation of insulin therapy that required basal insulin to achieve tolerable muscle symptoms and better glucose control, without the development of diabetic ketoacidosis.